1995
DOI: 10.1080/07263869500035531
|View full text |Cite
|
Sign up to set email alerts
|

Project renourish: A dietary intervention to improve nutritional status in people with multiple disabilities

Abstract: An in tervention was designed to improve the nutrition of underweight persons with multiple disabi fities who tived in a large institution. They were given an enriched diet, with increased energy density, for a year. Measurements of anthropometric status, biochemical status and cfinical measures such as antibiotic and suppository usage, were taken before the intervention, at 6 months, and at t 2 months. Basefine measures of the 6 9 subjects showed that they were severely underweight, and had levels of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…The results of the study are broadly consistent with previous research that has suggested that people with ID are at increased risk of being underweight, obese and leading sedentary lives (Beange et al. 1995a,b; Kennedy et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the study are broadly consistent with previous research that has suggested that people with ID are at increased risk of being underweight, obese and leading sedentary lives (Beange et al. 1995a,b; Kennedy et al.…”
Section: Discussionsupporting
confidence: 90%
“…(2000) reported prevalence rates of underweight of 22% of men and 22% of women among a sample of 500 adults with ID in various forms of supported accommodation in the UK (compared with 3% of men and 6% of women in the general population: National Centre for Social Research 2002). Beange et al. (1995a) identified 63% of an institutionalized sample of 131 adults with profound multiple disabilities as being underweight.…”
Section: Introductionmentioning
confidence: 99%
“…In people with ID, undernourishment, rather than over‐nutrition, traditionally has been a problem (Beange et al . ), but it may be that people with ID are displaying the same patterns as the general population: that is, tending to being over‐nourished (Tanumihardjo et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all have physical difficulties with food ingestion; a substantial percentage needs gastrointestinal feeding tubes. Difficulties with feeding may lead to dehydration and malnourishment (Beange et al 1995). Sleep disorders are also widespread among people with profound intellectual and multiple disabilities.…”
Section: Introductionmentioning
confidence: 99%